2012
DOI: 10.12693/aphyspola.121.a-32
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Vibroacoustic Climate Inside the Buses Solaris Urbino 12 Used in Public Transport Systems

Abstract: Despite new technological solutions and attempts to improve the working conditions during the operation of vehicles, city bus drivers are still exposed to negative impacts of noise and vibrations, causing stress, increased fatigue and lead to numerous diseases. Therefore it seems merited to investigate the acoustic climate (i.e. acoustic phenomena caused by the sources of noise of vibrations in the function of time and space) and the working conditions during the operation of Solaris Urbino 12 vehicles, widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…They found that the normalized exposure levels were all over 65 dBA in all cases making the work environment 'uncomfortable' according to the Brazilian Legislation for Ergonomics. Furthermore, Damijan [26] measured noise levels in the passenger section of buses and reported that the equivalent noise levels in the center and rear part of the buses during the ride were 62.4 dBA and 67.9 dBA respectively. The ANOVA test revealed that the bus type had a significant effect on the noise level inside the buses and the post-hoc analysis showed that, the difference in the noise level measured in the 3 types of buses was significant.…”
Section: Discussion 41 Noise Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the normalized exposure levels were all over 65 dBA in all cases making the work environment 'uncomfortable' according to the Brazilian Legislation for Ergonomics. Furthermore, Damijan [26] measured noise levels in the passenger section of buses and reported that the equivalent noise levels in the center and rear part of the buses during the ride were 62.4 dBA and 67.9 dBA respectively. The ANOVA test revealed that the bus type had a significant effect on the noise level inside the buses and the post-hoc analysis showed that, the difference in the noise level measured in the 3 types of buses was significant.…”
Section: Discussion 41 Noise Levelmentioning
confidence: 99%
“…The results of the present study indicated that the vibrations at the passenger seats were non uncomfortable vibrations. In contrast; Damijan [26] reported that vibration at the passenger seat during ride was 0.4 ms -2 which is considered as a little uncomfortable vibration according to ISO 2631-1-1997. Also, Okunribido et al [30] measured whole-body vibration transmitted to bus drivers and their results…”
Section: Whole-body Vibrationmentioning
confidence: 97%